AI-enabled individual entrepreneurship theory: redefining scale, capability, and sustainability in the digital age - Venkat Ram Reddy Ganuthula (Journal of Innovation and Entrepreneurship)
Abstract The AI-enabled individual entrepreneurship theory (AIET) redefines entrepreneurial dynamics in the AI-driven economy, empowering solo entrepreneurs to achieve scalability and sustainability traditionally reserved for large organizations. Addressing a gap in entrepreneurship frameworks, AIET integrates knowledge- and resource-based perspectives, proposing that AI enhances individual capabilities through interconnected mechanisms: skill augmentation, capital access, and risk reduction. Empirical evidence, including studies on AI-driven resilience, supports AIET’s claim that individuals can compete with larger firms. Five testable propositions examine AI’s impact on capabilities, market entry, and competition. Prioritizing sustainability, AIET aligns with SDGs, such as economic inclusion (SDG 8) and resource efficiency (SDG 12), fostering resilient innovation. While promising, AIET acknowledges limitations, such as ethical risks (e.g., algorithmic bias) and regional access disparities, urging further cross-cultural research. This model guides AI-oriented entrepreneurship, emphasizing sustainable, scalable ventures that redefine traditional organizational advantages.